STRATEGI PENERAPAN KEARIFAN LOKAL DALAM PENATAAN RUANG - Wiryananda, Ngakan Gede Agung Khrisna (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
The concept of local wisdom related to spatial planning has long been known to the public, but this concept is often ignored and hampered by various factors. So it is necessary to determine a strategy to apply the concept of local wisdom in spatial planning. This research uses a literature review method by conducting descriptive analysis. Local wisdom has the potential to prevent degradation and land conversion, become reference material in making Regional Regulations related to spatial planning, determining factors in spatial patterns and structures so that they remain distinctive, and supports compliance with Regional Regulations. On the other hand, spatial planning can provide protection for local wisdom so that it remains sustainable. The formulation of strategies that can be implemented so that local wisdom and spatial planning can be implemented well, namely in terms of spatial planning by involving the participation of indigenous communities, traditional leaders and religious leaders, conducting cross-disciplinary studies of local wisdom, and the existence of zoning or area regulations related to social culture. In terms of spatial utilization, this can be done by strengthening cooperation between Traditional Institutions/Traditional Villages with Regional Governments, establishing communication forums and information centers specifically for spatial utilization. The aspect of controlling spatial utilization is by synergizing customary security with the Regional Government and using a customary control system that does not conflict with formal rules.